Uninephrectomy in rats on a fixed food intake results in adipose tissue lipolysis implicating spleen cytokines - Arsenijevic, Denis; Cajot, Jean-Francois; Dulloo, Abdul G.; Montani, Jean-Pierre (Frontiers in Physiology, 2015)
The role of mild kidney dysfunction in altering lipid metabolism and promoting inflammation was investigated in uninephrectomized rats (UniNX) compared to Sham-operated controls rats. The impact of UniNX was studied 1, 2 and 4 weeks after UniNX under mild food restriction at 90% of ad libitum intake to ensure the same caloric intake in both groups. UniNX resulted in the reduction of fat pad weight. UniNX was associated with increased circulating levels of beta-hydroxybutyrate and glycerol, as well as increased fat pad mRNA of hormone sensitive lipase and adipose triglyceride lipase, suggesting enhanced lipolysis. No decrease in fat pad lipogenesis as assessed by fatty acid synthase activity was observed. Circulating hormones known to regulate lipolysis such as leptin, T3, ghrelin, insulin, corticosterone, angiotensin 1 and angiotensin 2 were not different between the two groups. In contrast, a select group of circulating lipolytic cytokines, including interferon-gamma and granulocyte macrophage–colony stimulating factor, were increased after UniNX. These cytokines levels were elevated in the spleen, but decreased in the kidney, liver and fat pads. This could be explained by anti-inflammatory factors SIRT1, a member of the sirtuins, and the farnesoid x receptor, which were decreased in the spleen but elevated in the kidney, liver and fat pads (inguinal and epididymal). Our study suggests that UniNX induces adipose tissue lipolysis in response to increased levels of a subset of lipolytic cytokines of splenic origin.